The Impact of Asthma Management Guideline Dissemination on the Control of Asthma in the Community - Robert L Cowie; Margot F Underwood; Sally Mack (Canadian Respiratory Journal)
OBJECTIVE: To measure the impact of asthma management education on the control of asthma in the community.